Rynkowe uwarunkowania rozwoju funduszy emerytalnych w kontekście przemian gospodarczych XX wieku - Winkler-Drews, Tadeusz (Market Background for Development of Pension Funds in the Context of Economic Change in 20th Century, 2006)
The purpose of this paper is to analyze the investment background for development of pension funds in the 20th century. The article discusses the number of the most important factors influencing the development of the common investment institutions in the most developed market economies of the 20th century. The article attempts to provide a synthetic assessment of the stock exchange situation in 20th century Europe, Asia and America, in the context of the investment horizon typical for pension funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 92-108